Physician Quality Reporting System - Anumula, N.; Sanelli, P.C. (American Journal of Neuroradiology, 2011)
SUMMARY: A brief review of the Physician Quality Reporting System (PQRS) is presented highlighting the program's legislative history, eligibility requirements and incentive payment plan. Specifically, PQRS measures applicable to neuroradiology practice are discussed. Several steps are suggested for individual physicians or group practices to start participation in the program. Resources are also provided for further information on the program requirements and PQRS measures. CMSCenter for Medicare and Medicaid ServicesPFSPhysician Fee Schedule